The Role of MAPK3/1 and AKT in the Acquisition of High Meiotic and Developmental Competence of Porcine Oocytes Cultured In Vitro in FLI Medium - Procházka, Radek; Bartková, Alexandra; Němcová, Lucie; Murín, Matej; Gad, Ahmed; Marcollová, Kateřina; Kinterová, Veronika; Lucas-Hahn, Andrea; Laurinčík, Jozef (International journal of molecular sciences, 2021)
The developmental potential of porcine oocytes cultured in vitro was remarkably enhanced in a medium containing FGF2, LIF and IGF1 (FLI) when compared to a medium supplemented with gonadotropins and EGF (control). We analyzed the molecular background of the enhanced oocyte quality by comparing the time course of MAPK3/1 and AKT activation, and the expression of genes controlled by these kinases in cumulus-oocyte complexes (COCs) cultured in FLI and the control medium. The pattern of MAPK3/1 activation in COCs was very similar in both media, except for a robust increase in MAPK3/1 phosphorylation during the first hour of culture in the FLI medium. The COCs cultured in the FLI medium exhibited significantly higher activity of AKT than in the control medium from the beginning up to 16 h of culture; afterwards a deregulation of AKT activity occurred in the FLI medium, which was not observed in the control medium. The expression of cumulus cell genes controlled by both kinases was also modulated in the FLI medium, and in particular the genes related to cumulus-expansion, signaling, apoptosis, antioxidants, cell-to-cell communication, proliferation, and translation were significantly overexpressed. Collectively, these data indicate that both MAPK3/1 and AKT are implicated in the enhanced quality of oocytes cultured in FLI medium.
Keywords: signální transdukce; Signal Transduction; LIF; IVM techniky; gene expression; AKT kinase; mitogenem aktivovaná proteinkinasa 1; Female; mitogenem aktivovaná proteinkinasa 3; Meiosis; oocyte maturation; Mitogen-Activated Protein Kinase 3; zvířata; Cells, Cultured; Culture Media; oogeneze; oocyty; kultivační média; Swine; oocyte competence; meióza; protoonkogenní proteiny c-akt; Proto-Oncogene Proteins c-akt; MAP kinase 3/1; ženské pohlaví; kultivované buňky; IGF1; In Vitro Oocyte Maturation Techniques; Animals; Oocytes; Mitogen-Activated Protein Kinase 1; prasata; FGF2; Oogenesis